Marginalization and Mobilization: The Roots of Female Legislators' Collaborative Advantage in the States. Issue 4 (19th December 2021) - Swift, Clint S.; VanderMolen, Kathryn
Abstract: Scholars have argued that female legislators are more prone to collaborate than their male counterparts. Though collaboration may be more or less evident in particular situations, we seek to more clearly establish the mechanism behind women's collaborative activity using the framework of marginalization. In this paper, we use cosponsorship data from 74 state legislative chambers from 2011–2014 to analyze collaborative patterns and mobilizing institutions. We find female legislators are more collaborative than men, and that their collaborative advantage strengthens in chambers where women are systematically excluded from leadership positions. The advantage also extends to bipartisan collaboration, but only in less polarized settings with women's caucuses. Furthermore, our findings imply that as women are integrated into leadership collaboration will actually decline, especially within their own party. We believe these results are important for understanding both the roots of collaborative behavior among female legislators and consequences of chambers that marginalize women from leadership positions.